Farmer's Perception of Climate Change and the Impacts on Livelihood in South Sulawesi. Issue 1 (August 2021) - Arifah,; Salman, D; Yassi, A; Demmallino, EB
Abstract: Climate change and variability have affected people, especially in developing countries whose livelihood depends upon agriculture. Smallholder farmers in South Sulawesi are identified as particularly vulnerable with climate change impact and have limited knowledge on how to make production decisions in uncertain environment. The farmer's perception and the impact of climate change are crucial factors that affect farm productivity and adaptation strategy. This study investigates the perceptions of farmers towards climate change and the impacts. Therefore, a cross-sectional survey was conducted with a random sample of 120 smallholders' farmers that were distributed into 4 districts in South Sulawesi. It was discovered that the majority of the respondents believed that climate change is real and about 83 percent of them acclaimed this phenomenon had caused negative effect on their livelihood. Some indications of the impact of climate change include increasing temperatures, and long dry seasons that had reduced rain-fed rice production. The results also indicate that pests and plant diseases had elevated in several places due to uncertain weather. In addition, climate change had influenced the availability of water sources. Hence, policy implications are that appropriate strategies are crucial to help farmers make adaptation choices in this situation.